PENGARUH PERSEPSI KEAMANAN, KUALITAS INFORMASI DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE (STUDY KASUS PADA KONSUMEN SHOPEE DI YOGYAKARTA) - Susanto, Dedek; Fadhilah, Muinah; Udayana, Ida Bagus Nyoman (Universitas Negeri Yogyakarta, 2021)
The study aims to analyze the partial and simultaneous effect of perceived security, information quality and trust on purchasing decisions with primary data from questionnaires. The population in this study were all Shopee consumers in Yogyakarta and the research sample was determined by probability sampling method with nonprobability sampling techniques so that 100 samples were obtained. This study uses multiple linear regression analysis with the results of the study concluded that simultaneously perceptions of security, information quality and trust affect purchasing decisions and partially security perception variables have no effect on purchasing decisions while information quality affect purchasing decisions. Keywords: Security Perception, Information Quality, Trust and Purchasing Decisions